Efektivitas Penerapan Model Environmental Learning untuk Meningkatkan Hasil Belajar Matematika Peserta Didik - Rismawati; Tayeb, Thamrin; Nur, Fitriani; Sulasteri, Sri; Mattoliang, Lisnasari Andi (Faculty of Tarbiyah and Teacher Training, 2024)
Effective mathematics learning is essential to equip students with logical and analytical thinking skills, especially in the 21st-century era that demands problem-solving competency and adaptation to complex challenges. However, the low mathematics learning outcomes in various schools indicate the need for a more interactive and contextual learning model. This study aims to determine the effectiveness of implementing the Environmental Learning model on students' mathematics learning outcomes, especially at MA Darul Fallaah Unismuh Makassar. This study uses a pre-experimental design method with a one-group pre-test post-test design approach involving one class as a sample. The main instrument used is a mathematics learning outcome test. The results of the study showed that there was a significant difference between students' mathematics learning outcomes after implementing the Environmental Learning model and students before implementing the Environmental Learning model. Thus, this model is effective for improving students' mathematics learning outcomes. Follow-up research can be conducted by testing the effectiveness of the Environmental Learning model at various levels of education or other subjects to expand the generalization of the results and understand its impact in different contexts.